Assessment of the level of knowledge and applicability of the International Classification of Functionality, disability and health (CIF) in physiotherapy professionals (Research, Society and Development, 2021)
Aim: The present study aimed to assess the level of knowledge and applicability of the ICF in physiotherapy professionals. Methods: This is an exploratory, descriptive cross-sectional study with a quantitative approach, involving physiotherapists who live in Pernambuco and are active in CREFFITO-1. The volunteers answered a questionnaire about the CIF developed by the researchers through the Google Forms platform. The collected data were tabulated by means of a spreadsheet, and this was presented descriptively and, later, having their results compared through tests considering the security level